GPS and GIS Based Delineation of Soil Micro and Secondary Nutrient Deficient-sufficient Areas of North Western Plateau Zone of Odisha, India - Jena, Bandita; Nayak, R. K.; Das , J.; Shivhare, S.; Mohapatra, S.; Sethy, D. (International Journal of Bio-resource and Stress Management, 2023)
Assessment and delineation of secondary and micronutrients plays pivotal role in sustainable agriculture. Blanket application of micronutrient fertilizers without the knowledge of native nutrient status may result in nutrient deficiency or toxicity. Since there exists a narrow gap between deficiency and toxicity range of micronutrients so judicious application is essential. Precise analysis by skilled persons and sophisticated instruments poses a drawback in its routine analysis at different places. AICRP on micronutrient project is undertaking analysis of micro and secondary nutrients precisely with precise collection soil sampling based on GPS to quality analysis through expert scientists. The present paper focuses on status of micro and secondary nutrients of Deogarh district of Odisha representing the north western plateau zone.From analysis of 208 no of georeferenced samples collected from 3 blocks of Deogarh highest deficiency of B to the extent of 90% of samples was observed followed by available Sulphur and DTPA extractable Zn. Whereas soils were quite sufficient with respect to Fe, Mn, Cu. Digitized soil fertility maps were prepared by using ARC GIS software which clearly delineated the district into zone of micro nutrient deficiency and sufficiency. These maps will be helpful for the farming community of the study zone to use properly the secondary nutrients and micro nutrients for different crops thereby saving costly inputs with increase in production, productivity, crop quality.